2015
DOI: 10.1039/c4fo00806e
|View full text |Cite
|
Sign up to set email alerts
|

Structural stability and Sin a 1 anti-epitope antibody binding ability of yellow mustard (Sinapis alba L.) napin during industrial-scale myrosinase inactivation process

Abstract: This study investigated the structural stability of yellow mustard (YM, Sinapis alba L.) napin and the changes of its Sin a 1 anti-epitope antibody-binding ability during myrosinase enzyme inactivation process. The food industry uses myrosinase-inactive non-pungent YM for uses beyond spice applications. Napin was isolated from seeds received from an industrial processor before (YM + M) and after (YM - M) myrosinase inactivation. Secondary and tertiary structural features and surface hydrophobicity parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…According to Monsalve et al [24], it is the linear epitope that is considered to be the antigenic determinant. Based on this epitope, an anti-epitope antibody for the quantification of Sin a 1 by a non-competitive enzyme linked immunosorbent assay was developed [43]. This same study also showed that the napin protein fraction of yellow mustard contained proteins devoid of the linear epitope sequence, thereby not contributing to all cases of 2S allergenicity.…”
Section: Resultsmentioning
confidence: 99%
“…According to Monsalve et al [24], it is the linear epitope that is considered to be the antigenic determinant. Based on this epitope, an anti-epitope antibody for the quantification of Sin a 1 by a non-competitive enzyme linked immunosorbent assay was developed [43]. This same study also showed that the napin protein fraction of yellow mustard contained proteins devoid of the linear epitope sequence, thereby not contributing to all cases of 2S allergenicity.…”
Section: Resultsmentioning
confidence: 99%